2016
DOI: 10.3928/01477447-20160517-01
|View full text |Cite
|
Sign up to set email alerts
|

Navigation Makes Transforaminal Lumbar Interbody Fusion Less Invasive

Abstract: The current study presents a navigated transforaminal lumbar interbody fusion (TLIF) technique that requires only a 4-cm incision to accomplish a single-level TLIF. The authors compared its efficacy and efficiency with those of conventional TLIF. Forty patients who were indicated for single-level lumbar fusion were included and randomized to either the navigated-TLIF group or the conventional-TLIF group. Intraoperative blood loss, operative time, incision length, complications, bed rest period, and length of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Eleven studies were reported in this systematic review, including four randomized controlled trials (RCT) 40,43,46,48 and seven nonrandomized controlled trials. 2,18,24,28,33,42,44 The summary of our extracted data and reported articles is presented in Based on our meta-analysis, there was no statistical significance between both procedures (P ≤ 0.071) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were reported in this systematic review, including four randomized controlled trials (RCT) 40,43,46,48 and seven nonrandomized controlled trials. 2,18,24,28,33,42,44 The summary of our extracted data and reported articles is presented in Based on our meta-analysis, there was no statistical significance between both procedures (P ≤ 0.071) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with Bovonratwet et al [ 19 ], who showed a significantly shorter mean LOS in the navigated group compared to conventional single-level instrumented posterior lumbar fusion. This finding may be associated with the minimally invasive nature of navigated techniques, which are performed percutaneously, thus making surgical incisions smaller, reducing surgical exposure, and consequently minimizing intraoperative blood loss, as also shown by Wang et al [ 20 ] Diminished blood loss and postoperative pain may result in lower rates of transfusion and complications, thus reducing the need for critical care and allowing for an early patient discharge [ 21 ].…”
Section: Discussionmentioning
confidence: 99%